Challenges and Opportunities of Small and Medium Enterprises Activities in Kabul City - Esmat, Ahmadullah (Journal of Social Sciences - Kabul University, 2022)
The activities of small and medium enterprises in the city of Kabul are facing many obstacles and problems that have made their development process slow. These challenges include lack of financial resources, management problems, capacity building, insecurity, administrative corruption, and other problems that have a negative impact on the development and expansion of small and medium enterprises. Are still, despite these problems, the potential investment opportunities in the field of agriculture, food industry, construction material production industry, health, education and technology can be mentioned here? Therefore, paying attention to this sector in meeting the internal needs of the country and its direct effects on the income of the country's nationals and in the same way on the national income of the country, which ultimately affects the increase in GDP and causes job creation and unemployment prevention. Paying attention to small and medium enterprises in Afghanistan, especially in Kabul city, is of particular importance because 80% of commercial activities and 50% of gross domestic revenue are obtained from this degree and it has provided good sources of work for 75% of people in the society.